MAKNA SIMBOLIK TRADISI MALAM MARINEK PADA SUKU BATAK MANDAILING DI DESA PASIR TUNTUNG - Ihdina Rahmadhani Hararap; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Malam Marinek is one of the traditions carried out by the Batak Mandailing tribe in Pasir Tuntung village. The implementation of the malam marinek tradition has a series of objects and processions contained in it, which along with the development of the times and culture that is dynamic in nature the implementation of this tradition begins to shift. The purpose of this study is to find out the symbolic meanings contained in the implementation of the malam marinek tradition. This research uses a quality method with a symbolic meaning approach. There were nine informants in this study, three traditional leaders, two naposo nauli bulung, two parents implementing traditions and two brides-to-be. The results of this study show that the symbolic meaning of the malam marinek tradition consists of the meaning of the symbolic situation, the meaning of the product of social interaction and the meaning of interpretation. The meaning of this symbolic situation includes both physical objects and social objects, the meaning of the product of social interaction includes the meaning of informants towards the implementation of the evening tradition and the meaning of interpetation includes the motivations and feelings of the bride-to-be as the recipient of the tradition. Keywords: Symbolic Meaning, Marinek Night Tradition, Mandailing Batak